2014
DOI: 10.1002/ieam.1529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating exposure and potential effects on honeybee brood (Apis mellifera) development using glyphosate as an example

Abstract: This study aimed to develop an approach to evaluate potential effects of plant protection products on honeybee brood with colonies at realistic worst-case exposure rates. The approach comprised 2 stages. In the first stage, honeybee colonies were exposed to a commercial formulation of glyphosate applied to flowering Phacelia tanacetifolia with glyphosate residues quantified in relevant matrices (pollen and nectar) collected by foraging bees on days 1, 2, 3, 4, and 7 postapplication and glyphosate levels in lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 8 publications
12
96
2
1
Order By: Relevance
“…1 l of 75–300 mg l −1 of technical grade glyphosate for 5 days. This was about 2–3% above mortality in control experiments (Thompson et al., ). In our study, mortality after contact with the recommended concentration was about 10–28% and about 6–24% above mortality in control experiments.…”
Section: Discussionmentioning
confidence: 67%
“…1 l of 75–300 mg l −1 of technical grade glyphosate for 5 days. This was about 2–3% above mortality in control experiments (Thompson et al., ). In our study, mortality after contact with the recommended concentration was about 10–28% and about 6–24% above mortality in control experiments.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study found no effects of GLY on brood survival, development or mean pupal mass in a realistic exposure scenario (Thompson et al, 2014). In that study, honeybee colonies were exposed to the herbicide when the glasshouse where the colonies were settled was sprayed with GLY (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, no cosolvent was required, and both stock solutions of glyphosate and AMPA test items were prepared in deionized water (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Test Substancesmentioning
confidence: 99%
“…The risk to honeybees and honeybee broods has also been assessed, with no effects on broods at concentrations as high as 300 mg acid equivalent (a.e. )/kg sucrose solution [10]. The chronic risk assessment for fish and aquatic invertebrates has also been recently addressed for AMPA [11].…”
Section: Introductionmentioning
confidence: 99%